THE EFFECT OF TOTAL ASSETS, OWN CAPITAL AND REVENUE ON THE REST OF BUSINESS RESULTS ON COOPERATIVE PARTNER MANDIRI INDRAGIRI HULU REGENCY - Angga Hapsila; Ivalaina Astarina; Gilang Ramadan (JURNAL MANAJEMEN DAN BISNIS, 2021)
This research is a quantitative research conducted totested and analyzed the effect of total assets, equity and income partially on the remaining operating results at the Mitra Mandiri Cooperative, Indragiri Hulu Regency. This study uses secondary data by looking at the financial statements of the Mandiri Mitra Cooperative. The author performs data processing using multiple linear regression which processes it using SPSS (statistical package for social science) version 21 to get the output to conclude the results of this study. From the results of the study, it can be concluded that the number of assets has a significant effect on the remaining operating results and own capital has a significant effect on the remaining operating results while partially income has no significant effect on the remaining operating results.